Methodology to find the load pattern of a lv distribution Feeder and optimal capacitor placement - Gajananan, A.; Fernando, M.A.R.M.; Atputharajah, A.; Karunarathna, C.A.B. (My University, 2011)
The problem of capacitor placement for loss reduction in distribution system has been researched well in the past. In this paper a concept has been developed to determine the load pattern of a distribution feeder. Then a simple methodology has been illustrated to select the optimal size and location of capacitors to be placed in LV distribution network. The objectives were to minimize peak power loss and to improve voltage profile. The concept was extended to maximize the monetary savings while reducing the power loss in the network.
Keywords: Load pattern; Capacitor